2005
DOI: 10.1128/jvi.79.21.13694-13704.2005
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Polypurine Tracts (PPTs) Affect the Rous Sarcoma Virus RNase H Cleavage Specificity and Reveal a Preferential Cleavage following a GA Dinucleotide Sequence at the PPT-U3 Junction

Abstract: Reverse transcription is catalyzed by the viral enzyme reverse transcriptase (RT). Retroviral RTs have two activities, a DNA polymerase that can copy both RNA and DNA templates and an RNase H that digests RNA if, and only if, it is hybridized to DNA. The RT of avian sarcoma leukosis viruses, of which Rous sarcoma virus (RSV) is a member, is found predominantly as a heterodimeric complex comprised of ␣ and ␤ subunits. The ␣ subunit (63 kDa) contains the polymerase and RNase H domains, and the ␤ subunit (95 kDa)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The data we previously obtained suggest that RSV RNase H cleaves the DuckHepBFlipPPT predominantly at one position within the PPT (Fig. 2), adding a 5Ј-ATGTA sequence onto the U3 end of the linear viral DNA (2). Coincidentally, the sequence of this added sequence matches positions ϩ2 to ϩ6 in U3.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The data we previously obtained suggest that RSV RNase H cleaves the DuckHepBFlipPPT predominantly at one position within the PPT (Fig. 2), adding a 5Ј-ATGTA sequence onto the U3 end of the linear viral DNA (2). Coincidentally, the sequence of this added sequence matches positions ϩ2 to ϩ6 in U3.…”
Section: Resultsmentioning
confidence: 97%
“…Using a modified mammalian cell in which the vector cannot replicate avoids the problem of viral spread; to get the relative titer, the titer was corrected for the amount of capsid protein. Previous work from our laboratory showed that the RNase H of RSV RT preferentially cleaves after the GA dinucleotide at the 3Ј end of the WT RSV PPT and that it preferentially cleaves after a GA in mutant vectors that contain PPTs from other retroviruses (2). At the sequence in the PPT of DuckHepBFlipPPT that is recognized as the PPT-U3 junction, there is a GT dinucleotide instead of a GA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that the PPT sequence is important for the proper generation and removal of the PPT primer by RNase H (7,8,14,15). We previously reported that alternate PPTs affected the specific cleavages that remove the PPT in a Rous sarcoma virus (RSV)-derived vector, RSVP(A)Z (3,4). One of the alternate PPTs, the duck hepatitis B virus PPT in the reverse orientation (DuckHepBFlipPPT), was preferentially cleaved by the RNase H of RSV reverse transcriptase in a way that added 5Ј-TACAT to the end of U3 (because it is the minus strand on the U3 end that is joined to host DNA by integrase [IN], the minus-strand sequence is shown).…”
mentioning
confidence: 99%